Assessment parameters for coal-fired generation plant site selection - Abbas, Ahmad Rosly; Low, K.S.; Ahmad, Mohd Noh; Chan, Jin Hooi; Sasekumar, A.; Abdul Ghaffar, Fauza; Salleh, Kharulmaini Osman; John, K.R.; Saad, Abdul Yamin; Zahari, Wan Aida Wan; Phua, Y.T.; Phua, Y.N.; et al. (Regional Energy Resources Information Center (RERIC), Asian Institute of Technology, 2005)
In order to meet future demand for electricity, Tenaga Nasional Berhad (TNB) is committed to the long-term strategic planning in locating statable sites for future development of power stations. Site selection is an important process in the early planning stage of any power plant development as it will have significant implications on the capital investment, operational as well as the environment and socio-economic costs of the power plant. The aim of this presentation is to briefly describe the ten (10) main assessment parameters having the most profound effects on the selection of potential coal-fired generation plant sites.: These assessment parameters were derived based on a survey of approximately 40 experts, comprising from various specialists such as engineers from TNB, senior officers from Department Of Environment Malaysia (DOE), scientist from University Malaya (UM) and a number of other independent consultants.